Diagnosis and digitization of Dantesque Code “Phillipps 9589” - Salvatore Lorusso; Andrea Natali; Chiara Matteucci; Raffaele Savigni (Conservation Science in Cultural Heritage, 2008)
This work concerns the study of Dante’s Code, illuminated on parchment, which is preserved at the Library of “Centro Dantesco dei Frati Minori Conventuali” in Ravenna. This Code is well-known by the international scientific Community as Phillipps 9589 and its notoriety is not only due to the fact that it’s the only Dante’s Palimpsest, but also because it preserves, at the scripto superior, one of the older witness of that branch of handwritten tradition of Dante’s Commedia named “Tradition a”, the so-called “old Vulgate”. The research, worked out for several stages, had aimed to examine the technical-diagnostic aspects, in particular the general purposes had been: – evaluation about the state of preservation; – materials characterization; – improvement of the legibility of Dante’s text and Palimpsest reading; – evaluation about the preservative environment; – code digitization suitable for a intranet and internet use. In this connection, the following non-destructive diagnostic techniques bad been employed, also related to a documentary aim: – image analysis videomicroscope; – spectrophotometric colorimetry; – X-ray fluorescence (XRF); – Multispectral Imaging System (MuSIS); – environmental monitoring Instruments (thermohygrometer, illuminometer, aerosol spectrometer PTS e PM10).